Construction of the particle simulation model for ginger-soil system using discrete element method - Wang, Wenlong; Zhang, Pengcheng; Wang, Xin; Meng, Xiaojun; Wang, Fangyan (International Journal of Agricultural and Biological Engineering, 2024)
In order to systematically obtain the excavation characteristic parameters for ginger harvesting, experimental analysis was conducted on the discrete elemental parameters in a particle simulation model of the ginger-soil system. Through stacking tests, the surface energy of soil-ginger tuber JKR was determined to be 3.7 J/m2, the coefficient of static friction of soil-steel (65 Mn) was 0.56, the coefficient of rolling friction was 0.03, and the coefficient of restitution of collision was 0.40. Utilizing normal and lateral compression tests conducted on the soil body, the soil base parameters required for the Bonding model were determined. Subsequently, a three-dimensional model of ginger root and stem was constructed using these parameters. With the aid of 3D scanning technology, a discrete element parameter model was established for the ginger field during the harvesting period. On the basis of the measured parameters, a three-dimensional model of ginger rhizome was established and finally a discrete parameter model of ginger field was constructed in the harvesting period. The calibration parameters are highly reliable after the model’s tightness and field harvesting test, which provides reliable data support for the soil flow and the force of the soil-touching parts during the later simulation of ginger harvesting and digging operation. Keywords: ginger, soil, discrete element, simulation parameters, calibration DOI: 10.25165/j.ijabe.20241705.9102 Citation: Wang W L, Zhang P C, Wang X, Meng X J, Wang F Y. Construction of the particle simulation model for ginger-soil system using discrete element method. Int J Agric & Biol Eng, 2024; 17(5): 58-64.